EVALUASI PARADIGMA KRITIS TERHADAP INTEGRASI, KONEKSI, DAN APLIKASI DALAM METODE KADIR PADA PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN NILAI NILAI ISLAM - Ainurrafiq Dawam; M. Al Haris (Jurnal Karya Pendidikan Matematika, 2025)
This study evaluated the effectiveness of the KADIR method (Connection, Application, Discourse, Improvisation, and Reflection) in integrating Islamic values into mathematics education. The KADIR method aimed to enhance conceptual understanding, critical thinking skills, and student motivation by connecting mathematical concepts with Islamic values. Using a qualitative literature-based approach, this study found that the KADIR method effectively improves students' understanding of mathematical concepts and their application in everyday life. Integrating Islamic values through this method also strengthens students' character and morals and increases their motivation to learn. The main challenges in implementing this method included the limitations of resources and support for teachers, as well as the complexity of connecting mathematical concepts with Islamic values. This study provided theoretical and practical contributions to the development of a holistic mathematics learning model. Recommendations for educators included competency development through training, the design of contextual learning, and the implementation of holistic evaluation. These findings were expected to improve the quality of mathematics education and help students develop a more comprehensive and meaningful understanding of the context of Islamic values.